Green growth and travelism concept, policy and practice for sustainable tourism - DeLacy, Terry; Min,Jiang; Lipman,Geoffrey; Vorster,Shaun (Contemporary geographies of leisure, tourism and mobility., 2014)
"This significant volume is the first to bring together research, policy and practice on the implications of the rapidly evolving green growth paradigm on the tourism sector. It provides a conceptual discussion of the implications of the new development trend for key players; consumers, firms and destinations of the travel and tourism system. It integrates case studies that highlight key issues in the emerging developing markets and explores the policy settings and frameworks that underpin tourism growth towards the green economy. This is essential reading for all those interested in Tourism and Development Studies" -- Provided by publisher.